Konsepsi Ahliyah dalam Transaksi Ekonomi Syariah - M. Arif Al- Kausari (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2020)
This research discusses the concept of an expert in the KHES which is a guideline for shari'ah economic practitioners so that the Compilation of Sharia Economic Laws should be a study. Especially for experts (who are capable of law), it is quite an important discussion to be parsed, studied and discussed. Given that legal competence has an important position in the contract because it is a condition that must be met by the contract subject which implies that the contract can be considered valid or not. In this research, the researcher examines the concept of expert in KHES from the perspective of Islamic law (the opinion of the ulama) which is contained in fiqh books, as well as the integration of existing regulations in Indonesia. The purpose of this study is to provide an understanding of the community as legal subjects, so that the contracts they do are not only correct under Islamic law, but also not against Indonesian positive law. Besides that, as a guideline for economic or legal practitioners, the existing articles must be studied. So that in this study there were things that the researchers found in KHES that needed to get additional, namely, barriers to skills. This research is in the form of literature using a normative-juridical approach, where most of the data sources are in the form of fiqh literature, and books relating to research material. It is said to be normative-juridical, because this research examines a legal norm, namely legislation with legal doctrine analysis. So that in this study the researchers describe in a qualitative-descriptive form. The legal competence referred to in KHES is actually an expertyatul ada '(active skill) in fiqh or ushul fiqh. Legal competence in KHES applies to personal legal subjects and legal entities, the requirements that must be possessed by personal legal subjects are adults at the age of 18 or married. As for a legal entity it can be considered legally competent if it does not fail. The provision of legal competence with these conditions is more inclined to the opinion of the hanafi school, both according to Imam Hanafi himself and according to Abu Yusuf and Muhammad Ibn Hasan.